2014
DOI: 10.1177/0269215514538981
|View full text |Cite
|
Sign up to set email alerts
|

Pilates improves pain, function and quality of life in patients with chronic low back pain: a randomized controlled trial

Abstract: The pilates method can be used by patients with LBP to improve pain, function and aspects related to quality of life (functional capacity, pain and vitality). Moreover, this method has no harmful effects on such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
98
4
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(131 citation statements)
references
References 27 publications
10
98
4
19
Order By: Relevance
“…Table 1: Outcome measures at baseline and after the 6-week control period. The results of the present investigation are in accordance with Taylor et al [35] and Natour et al [29] who observed improvements in pain and self-reported disability after 6 and 12-week Pilates interventions respectively. Importantly our study observed mean decreases of 33% in the ODQ and 15mm in VAS scores which represents a clinically meaningful change [21,24].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Table 1: Outcome measures at baseline and after the 6-week control period. The results of the present investigation are in accordance with Taylor et al [35] and Natour et al [29] who observed improvements in pain and self-reported disability after 6 and 12-week Pilates interventions respectively. Importantly our study observed mean decreases of 33% in the ODQ and 15mm in VAS scores which represents a clinically meaningful change [21,24].…”
Section: Discussionsupporting
confidence: 93%
“…Richmond [39] suggested exercise that transcends into integrated movement may improve resistance to fatigue of muscles associated with maintaining balance after a postural perturbation. CE improved post-intervention which is in accordance with the work of Natour et al [29] who purported that Pilates improved core strength because of higher levels of TrA contraction. In addition Kamioka et al [28] reported that there was strong evidence that in a healthy population Pilates exercise improved flexibility and enhanced muscular endurance in the short term.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations